Self-awareness of diabetes mellitus and prediabetes status among patients with overweight in the Jember area - Sukma, Anindianti; Sutawardana, Jon Hafan; Kushariyadi, Kushariyadi (University of Muhammadiyah Malang, 2023)
Introduction: People who are excess weight have expanded insulin resistance and the development of high blood sugar, which drives prediabetic status and later generates diabetes mellitus. Someone can experience prediabetes for several years, but they don't know any symptoms. Ultimately, they experience health problems leading to type 2 diabetes mellitus. Patients who are overweight lack self-awareness about diabetes mellitus (DM). Objectives: This research aims to determine the relationship between self-awareness and prediabetes status in overweight patients. Method: This research uses an analytic design with a cross-sectional approach. There were 84 respondents obtained from the accidental sampling technique. Data were collected from the Self Awareness Diabetes Mellitus questionnaire and random blood glucose results. Data were analyzed using Spearman rank with a significance value of 0.05. Result: The results showed a significant relationship between self-awareness about DM and prediabetes status with a negative correlation (p < 0.001; r = 0.678). This correlation means that the higher the self-awareness, the lower the respondent has prediabetes. In overweight patients, fat accumulation in the body can reduce insulin action, affecting prediabetes. Self-awareness is an attitude that someone with excess body weight must possess to prevent prediabetes. Conclusion: This study revealed the importance of increasing self-awareness and enforcing blood glucose control routinely so that someone who has entered the prediabetes category can enhance their lifestyle to stop diabetes mellitus.